2008
DOI: 10.1111/j.1468-5957.2008.02104.x
|View full text |Cite
|
Sign up to set email alerts
|

Performance‐vested Stock Options and Earnings Management*

Abstract: This paper investigates the effects of performance-vested stock options (PVSOs) on the propensity of managers to engage in earnings management. Using observations from the 240 largest non-financial firms in the UK, I show that managers are more likely to engage in earnings management when they hold a larger proportion of their compensation in PVSOs. When categorizing PVSOs on the basis of their distance from the end of performance periods, the results show that managerial incentives to manage earnings mainly s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
45
0
4

Year Published

2008
2008
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(49 citation statements)
references
References 72 publications
0
45
0
4
Order By: Relevance
“…The table below lists the countries for which data were obtained detailing the percentage number of women on the corporate board or equivalent highest decision-making body. Management Diagnostics Limited which has been successfully used in academic research (Singh, 2007;Kuang 2008;Fracassi and Tate, 2008) and which is rapidly establishing itself as the premier source of board-related data (Fernandes, 2009 BoardEx was used to identify percentage number of women both at the country and at the industry level. At the industry level firms were classified based on Standard Industrial Classification (SIC) codes to enable industry evaluation of the prevalence on women board directors.…”
Section: Dependent Variable: Sampling and Data Collectionmentioning
confidence: 99%
“…The table below lists the countries for which data were obtained detailing the percentage number of women on the corporate board or equivalent highest decision-making body. Management Diagnostics Limited which has been successfully used in academic research (Singh, 2007;Kuang 2008;Fracassi and Tate, 2008) and which is rapidly establishing itself as the premier source of board-related data (Fernandes, 2009 BoardEx was used to identify percentage number of women both at the country and at the industry level. At the industry level firms were classified based on Standard Industrial Classification (SIC) codes to enable industry evaluation of the prevalence on women board directors.…”
Section: Dependent Variable: Sampling and Data Collectionmentioning
confidence: 99%
“…Second, the extant research shows that some firms have higher incentives to manage earnings than others do and, therefore, in order to increase the power of the results, we repeat our analysis using a sample of firms that have a strong motivation to manage earnings. Prior studies (for example, Baker et al 2003;Bergstresser and Philippon 2006;Cheng and Warfield 2005;Kuang 2008;McAnally et al 2008) have showed that CEOs with high stock ownership tend to engage more in earnings management in Table 4 The association between female CEOs and classification shifting (firms with income-decreasing SPI)…”
Section: Robustness Analysesmentioning
confidence: 99%
“…Johnson, Ryan, andTian (2009) andErickson, Hanlon, andMaydew (2006) document a positive association between equity-based compensation and a firm being accused of fraud by the SEC. Similarly, Richardson, Tuna, and Wu (2003), Burns and Kedia (2006), and Kuang (2008) find that the likelihood of earnings restatement is positively related to equity-based compensation. Also, Chen, Chung, and Wynn (2009) find that audit fees are higher when internal audit managers receive incentive based compensation.…”
Section: Hypothesis Developmentmentioning
confidence: 89%